1990
DOI: 10.1073/pnas.87.14.5504
|View full text |Cite
|
Sign up to set email alerts
|

DNA-looping and enhancer activity: association between DNA-bound NtrC activator and RNA polymerase at the bacterial glnA promoter.

Abstract: The NtrC protein activates transcription of the ginA operon of enteric bacteria by stimulating the formation of stable "open" complexes by RNA polymerase (oMholoenzyme form). To regulate the ginA promoter, NtrC binds to sites that have the properties of transcriptional enhancers: the sites will function far from the promoter and in an orientation-independent fashion. To investigate the mechanism of enhancer function, we have used electron microscopy to visualize the interactions of purified NtrC and RNA polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
168
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(174 citation statements)
references
References 37 publications
5
168
0
1
Order By: Relevance
“…Evidence for this interaction was obtained in gel mobility shift assays, in which VirR bound to the VirR boxes was required for the efficient and specific binding of CpRNAP to the pfoA promoter. These results are in agreement with those of other studies that have shown that response regulators can interact with components of RNA polymerase (20,26,45,46).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Evidence for this interaction was obtained in gel mobility shift assays, in which VirR bound to the VirR boxes was required for the efficient and specific binding of CpRNAP to the pfoA promoter. These results are in agreement with those of other studies that have shown that response regulators can interact with components of RNA polymerase (20,26,45,46).…”
Section: Discussionsupporting
confidence: 83%
“…Alternatively, activators such as NtrC (24) and NifA (10) stimulate the isomerization of bound RNA polymerase from a closed complex to an open complex (29). It is unlikely that VirR would act in the same fashion as NtrC and NifA, as these proteins bind well upstream of the promoter (9,46). In contrast, the VirR boxes are located immediately upstream of the Ϫ35 box of the pfoA promoter region.…”
Section: Discussionmentioning
confidence: 99%
“…The activator converts the closed promoter complex to an open complex that is transcriptionally competent (Sasse-Dwight and Gralla, 1988;Morett and Buck, 1989;Popham et al, 1989;Lee et al, 1993;Lee et al, 1994;Perez-Martin and de Lorenzo, 1996b). To catalyse this isomerization, the activator must hydrolyse ATP (Weiss et al, 1991;Lee et al, 1993;Lee et al, 1994;Perez-Martin and de Lorenzo, 1996b) and make productive contact with 54 -holoenzyme through a DNA loop (Buck et al, 1987;Su et al, 1990;Wedel et al, 1990). Interactions between the activator and 54 -holoenzyme are transient, and sites involved in proteinprotein interaction have not been identified in these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Isomerization of the closed complex to transcriptionally competent open complexes requires an activator protein bound to a DNA sequence with enhancer-like properties (7,8) and nucleoside triphosphate hydrolysis by the activator protein (5,9,10). Activation appears to involve direct contact between activator and the holoenzyme (11)(12)(13).…”
mentioning
confidence: 99%